Study of The Change in The Chemical Specifications of Drinking Water in The Feeding Stations of the City of Sabratha Between the Past Two Decades and The Present. (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
Due to the increase in demographic growth and the location of the tourist city of sabratha, and the lock of rain rates in recent years, the demand for water has become increased, , which prompted curiosity to study changes in the specifications of the water specification of the stations feeding the city, in order to measure the physical in (pH, total dissolved salts, and electrical conductivity) and chemical indicators, such as  chloride, sulfate, calcium, magnesium, sodium, potassium and bicarbonate ions, also indicators of a common nature with bacteriology (NH4+, NO3-, NO2-). The feeding stations for the city were counted, and there were six operating stations as well as the ones that were not working six samples were drawn and the statistical analysis program (Excel) was used. This paper assessed the extent of the water deterioration of the drinking groundwater feeding the city over the period from 2001 to 2021 and comparing it with the Libyan standard specifications, the results showed a noticeable discrepancy over these years.
Keywords: aqueous degradation; city of Sabratha; chemical indicators; physical indicators; bacteriological contamination